Pelatihan Kecerdasan Buatan Menggunakan Teachable Machine untuk Siswa SMA Kelas XI - Catherine Olivia Sereati; Ferry Rippun Gideon Manalu; Pascalis; Yudha Harnoko; Melisa Mulyadi; Sandra Octaviani B. Widiarto; Linda Wijayanti; Karel Octavianus Bachri; Widodo Widjaja Basuki; FLORENTIA ANGELINA (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2026)
Digital literacy is crucial today, especially as artificial intelligence (AI) technology begins to develop. AI technology is widely discussed because it can help to improve efficiency in various fields of activity. The development of AI technology is basically aimed at improving human welfare, but there are disadvantages when AI technology is not used properly, which can harm society. To achieve beneficial outcomes and avoid the harm caused by the misuse of AI technology, it is deemed necessary to provide AI technology training to the community as early as possible. This community service activity provided AI training to students from Strada Santo Thomas Aquino High School, which has a mission that strongly supports the objectives of this training. This training activity began with an introduction to AI technology, which aimed to make students familiar with and understand the features of AI technology so that they are aware of the existence of AI around them. Students were explained how AI works, from database collection to pattern recognition, and were made aware that the use and development of AI technology must be carried out ethically and responsibly. The training method included an explanation of the importance and dangers of AI technology through presentations, discussions, and teamwork using the